2019
DOI: 10.3389/fmicb.2018.03308
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Hemorrhagic Disease Virus Non-structural Protein 6 Induces Apoptosis in Rabbit Kidney Cells

Abstract: Rabbit hemorrhagic disease (RHD) is a highly contagious disease caused by rabbit hemorrhagic disease virus (RHDV). Previous research has shown that RHDV induces apoptosis in numerous cell types, although the molecular mechanisms underlying the apoptosis induced by RHDV are not well understood. One possible factor is non-structural protein 6 (NSP6), a 3C-like protease that plays an important role in processing viral polyprotein precursors into mature non-structural proteins. To fully establish a role for NSP6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…Currently, no criteria have been developed to select phages for phage cocktail preparation due to the limited availability and the great diversity of phages. In our previous study, a phage cocktail containing only two phages with divergent genomes showed higher antimicrobial activity than other cocktails and any single phage (Chen et al, 2018). The divergent genomes of the selected phages imply that heterogeneous infection mechanisms against their hosts could be employed by the phages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, no criteria have been developed to select phages for phage cocktail preparation due to the limited availability and the great diversity of phages. In our previous study, a phage cocktail containing only two phages with divergent genomes showed higher antimicrobial activity than other cocktails and any single phage (Chen et al, 2018). The divergent genomes of the selected phages imply that heterogeneous infection mechanisms against their hosts could be employed by the phages.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the cultures were centrifuged again at 8,000× g for 10 min, and the supernatants were then filtered through the 0.22-μm pore-size membrane. The bacteriophage titer of the filtrate was determined using the double-layered method (Chen et al, 2018). Clear phage plaques were picked from the plates and placed into 1 ml of sterile 2216E medium.…”
Section: Methodsmentioning
confidence: 99%
“…RHD-related death can also be caused directly by systemic hemorrhagic diathesis and disseminated intravascular coagulation (DIC) [4], likely due to liver cell damage from apoptosis induced by RHDV [8,14]. A study on the normal rabbit kidney epithelial (RK13) and human liver hepatocellular (HepG2) cell lines [15] showed that RHDV non-structural protein 6 (NSP6) can induce apoptosis in host cells and is likely an important factor of RHD pathogenesis. In addition, it has been found that N-acetylcysteine [9], cardiotrophin [16], and melatonin [17] can alleviate liver damage and prolong the lives of rabbits infected with RHDV, likely due to the induction of various antiapoptotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that various viral proteins initiated the programmed cell death in different manners during virus infection [16,17,44,45]. In the study, four cell death-related ASFV proteins were identified, including pE199L and pE183L.…”
Section: Discussionmentioning
confidence: 92%